Novel Bathymetry of Lake Afdera Reveals Fault Structures and Volcano-Tectonic Features of an Incipient Transform Zone (Afar, Ethiopia) - Schaegis, Jean-Charles; Rime, Valentin; Kidane, Tesfaye; Mosar, Jon; Gebru, Ermias Filfilu; Atnafu, Balemwal; Foubert, Anneleen (Frontiers in Earth Science, 2021)
Lake Afdera is a hypersaline endorheic lake situated at 112 m below sea-level in the Danakil Depression. The Danakil Depression is located in the northern part of the Ethiopian Afar and features an advanced stage of continental rifting. The remoteness and inhospitable environment explain the limited scientific research and knowledge about this lake. Bathymetric data were acquired during two weeks expeditions in January/February 2016 & 2017 using an easily deployable echosounder system mounted on an inflatable motorized boat. This study presents the first complete bathymetric map of the lake Afdera. Bathymetric results show that the lake has an average depth of 20.9 m and a total volume of 2.4 km3. The maximum measured depth is 80 m, making Lake Afdera the deepest known lake in Afar and the lowest elevation of the Danakil Depression. Comparison with historical reports shows that the lake level did not fluctuate significantly during the last 50 years. Two distinct tectonic basins to the north and the south are recognized. Faults of different orientations control the morphology of the northern basin. In contrast, the southern basin is affected by volcano-tectonic processes, unveiling a large submerged caldera. Comparison between the orientation of faults throughout the lake with the regional fault pattern indicates that the lake is part of two transfer zones: the major Alayta – Afdera Transfer Zone and the smaller Erta Ale – Tat’Ali Transfer Zone. The interaction between these Transfer Zones and the rift axis forms the equivalent of a developing nodal basin which explains the lake’s position as the deepest point of the depression. This study provides evidence for the development of an incipient transform fault on the floor of the Afar depression.